Three dimensional atom probe and first-principles studies on spinodal decomposition of Cr in a Co-alloyed maraging stainless steel. (August 2016) - Tian, Jialong; Wang, Wei; Yin, Lichang; Yan, Wei; Shan, Yiyin; Yang, Ke
Abstract: The effect of Co addition on spinodal decomposition of Cr in a new maraging stainless steel was investigated by three dimensional atom probe (3DAP). The concentration profile of Cr and analysis by maximum likelihood method indicated an increase of spinodal decomposition amplitude of Cr in the Co-alloyed maraging stainless steel. The first-principles calculations showed that the increased Fe-Fe ferromagnetic interaction caused by Co addition might facilitate the formation of Cr-rich clusters in bcc Fe. Graphical abstract: